Multi-trait and cross-population genome-wide association studies across autoimmune and allergic diseases identify shared and distinct genetic component. Issue 9 (26th June 2022) - Shirai, Yuya; Nakanishi, Yoshimitsu; Suzuki, Akari; Konaka, Hachirou; Nishikawa, Rika; Sonehara, Kyuto; Namba, Shinichi; Tanaka, Hiroaki; Masuda, Tatsuo; Yaga, Moto; Satoh, Shingo; Izumi, Mayuko; et al.
Abstract : Objectives: Autoimmune and allergic diseases are outcomes of the dysregulation of the immune system. Our study aimed to elucidate differences or shared components in genetic backgrounds between autoimmune and allergic diseases. Methods: We estimated genetic correlation and performed multi-trait and cross-population genome-wide association study (GWAS) meta-analysis of six immune-related diseases: rheumatoid arthritis, Graves' disease, type 1 diabetes for autoimmune diseases and asthma, atopic dermatitis and pollinosis for allergic diseases. By integrating large-scale biobank resources (Biobank Japan and UK biobank), our study included 105 721 cases and 433 663 controls. Newly identified variants were evaluated in 21 778 cases and 712 767 controls for two additional autoimmune diseases: psoriasis and systemic lupus erythematosus. We performed enrichment analyses of cell types and biological pathways to highlight shared and distinct perspectives. Results: Autoimmune and allergic diseases were not only mutually classified based on genetic backgrounds but also they had multiple positive genetic correlations beyond the classifications. Multi-trait GWAS meta-analysis newly identified six allergic disease-associated loci. We identified four loci shared between the six autoimmune and allergic diseases (rs10803431 at PRDM2, OR=1.07, p=2.3×10 −8, rs2053062 at G3BP1, OR=0.90, p=2.9×10 −8, rs2210366 at HBS1L, OR=1.07, p=2.5×10 −8 in Japanese and rs4529910 at POU2AF1, OR=0.96, p=1.9×10 −10 across ancestries). Associations of rs10803431 and rs4529910 were confirmed at the two additional autoimmune diseases. Enrichment analysis demonstrated link to T cells, natural killer cells and various cytokine signals, including innate immune pathways. Conclusion: Our multi-trait and cross-population study should elucidate complex pathogenesis shared components across autoimmune and allergic diseases.